The Impact of Financial Knowledge, Past Experience, and Current Income on the Stock Investment Performance of Individual Investors - Gunawan Bunardi; Sarwo Edy Handoyo (Master of Management, School of Business and Management, Petra Christian University, 2025)
The study investigates the impact of financial knowledge, experience, and current income on the stock investment performance of individual investors in Indonesia. Using a quantitative descriptive approach, data were collected from 77 respondents through questionnaires and analyzed using multiple regression. The findings reveal that financial knowledge significantly enhances investment performance by improving decision-making, risk management, and portfolio diversification. Experience plays a pivotal role in helping investors adapt to market dynamics and refine strategies, positively impacting their performance. However, current income does not significantly influence investment performance, indicating that non-financial factors also shape investment success. This research contributes to the understanding of key factors influencing investment returns and provides practical insights for financial education and policy development, empowering individual investors to achieve better outcomes.